Energy Performance Certificate for buildings as a strategy for the energy transition: Stakeholder insights on shortcomings. Issue 2 (November 2020) - Cozza, Stefano; Chambers, Jonathan; Brambilla, Arianna; Patel, Martin K
Abstract: Improving building performance is key to tackling the challenges of climate change, considering that buildings account for 40% of the global energy consumption. The urgent need for energy efficiency improvement of buildings calls for the implementation of suitable policy instruments, including performance assessments. Currently, the performance of buildings is officially assessed by Energy Performance Certificate (EPC) schemes. However, EPCs certify the design more than the building, relying on simulations and assumptions rather than on the buildings' actual demand for energy which is partly determined by occupant behaviour, execution of the work and malfunctioning of the equipment. This work investigates how the governance of the performance certification scheme could be improved with the objective of a more robust EPC scheme. Based on a qualitative study through interviews with energy experts the current EPC system in Switzerland is characterized, allowing to understand important limitations. The insights help to shape a list of recommendations for further development of the EPC scheme. This research is relevant because the failure to correctly assess building performance leads to excess carbon emissions and higher energy costs, undermining the attainability of the energy policy targets.